PENGARUH MUTU PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA KOPERASI SEPAKAT JAYA MANDIRI DI BANDAR LAMPUNG - -, Sodirin (Jurnal Manajemen dan Keuangan, 2012)
Cooperative Agree Bandar Lampung Jaya Mandiri is engaged in cooperative savings and loans, credit and provision of basic food items. Confidence in implementing cooperative systems provide capital loans to its members, so it does not need any guarantee or collateral. Problems faced by Cooperative Agree Jaya Mandiri Bandar Lampung is the number of cooperative members are steadily decreasing from 2001 until 2010. The problems are formulated: Is the consumers perception of Cooperative Agree Jaya Mandiri Belfast on dimensions of quality of service that consists of physical evidence (tangibles), reliability (reliability), responsiveness (responsiveness), assurance (assurance), and empathy (empathy) affect the customer satisfaction? The purpose of this thesis is to investigate the effect of consumer perceptions of Cooperative Agree Jaya Mandiri Belfast on dimensions of quality of service consisting of tangibles, reliability, responsiveness, assurance, and empathy towards customer satisfaction, and as a contribution to the cooperative thinking in its efforts to provide the best service to members. The hypothesis put forward by the author are: the quality dimensions of tangibles, reliability, responsiveness, assurance, and empathy at the Cooperative Agree Jaya Mandiri Bandar Lampung effect on customer satisfaction. Conclusions can be drawn that the hypothesis of the authors received, that there is influence between the services of Cooperative Agree Jaya Mandiri Belfast are: Tangible, Reliability, Responsiveness, Assurance, Emphaty of member satisfaction. It is based on Chi Square test with 95% confidence level and degrees of freedom 4, X2hitung each factor that is Tangible, Reliability, Responsiveness, Assurance, Emphaty>X2 table, so Ho rejected and Ha accepted.Keywords: Quality of Service and Customer Satisfaction